The Future of Mining: Will in Place Recovery Ever Come of Age? - R. Batterham (International Mineral Processing Congress, 2018)
"The history of mineral processing is indeed long and has always been tied to mining methods of the day. While many new processes and devices have been developed, the most significant trend in recent times has been the ever increasing scale of operations. There is serious doubt this ongoing trend is enough to match the global trend of falling grades and rising energy demands needed for mineral processing. As well we see that globally, the social licence to operate for mining (and hence mineral processing) is far from secure. Indeed, some argue that mining as we know it is dying and in the future, mining will be much more environmentally secure, even to the extent of insisting upon “in place” recovery and only bringing to the surface the valued product. In this paper we comment on the ramifications of broader uptake of more sustainable mining for mineral processing methods and address the specific question of whether recent progress in in place recovery will lead to a timely breakthrough. The answer proposed is that this is possible in the next 10 - 20 years but in the meantime, the focus is just as likely to be on removal of waste much earlier in circuits. Either way, mineral processing as we know it will change significantly. INTRODUCTION Mineral processing has a long history well covered in a recent publication (Habashi, 2006) who points out “the ancient Egyptians knew already that it would be easier to melt an earth rich in gold particles than another which is poor. As a result, all efforts were made to enrich the gold by washing away the light gangue minerals. Similarly, another ancient method for enriching gold particles from a river stream was by means of fleece, hence the Greek myth of the “golden fleece”. Since the middle ages, striving for improved economics has driven a string of innovative developments in milling and separation. The reader is again referred to the informative and illustrative text by Habashi."